Knowledge appropriation and identity: toward a multi-discourse analysis - Kamoche, Ken; Beise-Zee, Rian; Mamman, Aminu (SAGE, 2014)
Knowledge appropriation has been underpinned by an assumption of the organization’s ‘entitlement’ to appropriate knowledge and the outcomes of its utilization. Given the complexity of knowledge and the potentially conflicting views held about it, this assumption is revealed to be theoretically imprecise in the way it marginalizes alternative voices through the pursuit of competitive advantage and ‘value capture’. We attribute this approach to the functionalist analytical lens which sees knowledge as an asset appropriable almost exclusively by the organization in the form of financial/economic ‘rents’. In order to advance understanding of the multi-faceted nature of the organization-individual appropriation regime, we make the case for an expansion of the discursive space for talking about the phenomenon, and posit the concept of ‘property in knowledge’ which we tie to the way individuals construct their identities.